Discharge by Noon: A Checklist Initiative by the Otolaryngology Service. (8th May 2020) - Tamaki, Akina; Cabrera, Claudia; Hoppe, Kathryn; Maronian, Nicole
Abstract : Objectives/Hypothesis: Hospital length of stay (LOS) and throughput are critical issues for hospitals. Late hospital discharges contribute to bottlenecks in the emergency department, overcrowd surgical and procedural areas, and limit patient tertiary‐care center transfers. Our goal was to increase discharge by noon (DCBN) percentage from 8% to over 50% in a sustainable manner. Study Design: Retrospective Review. Methods: We used a multiple time series design and a quality improvement approach. An interdisciplinary improvement team (IIT) identified the main causes contributing to late discharge and then developed and implemented multiple interventions to increase the percentage of DCBN. Admissions and discharge information were obtained for all patients in the otolaryngology service (January 2014–September 2017). The intervention was implemented in July 2015. The primary outcome was the percentage of DCBN per month. Secondary outcomes were LOS, case‐mix index (CMI), patient experience, and 30‐day readmissions. We analyzed the impact of our intervention and outcomes at the preintervention, peri‐intervention, and postintervention periods. Results: One thousand four hundred sixty‐four admissions to the otolaryngology service were included. Throughout the intervention period, the percentage of patients DCBN increased. Analysis of the intervention showed significant DCBN change of 15% in the first versus 42% in the last 12‐months ( P < .001), and shorter LOS (−1.4 days, P < .001) and lower CMI (−0.6, P < .001) in the DCBN group. Patient satisfaction scores improved by 4% ( P < .05), and no difference in 30‐day readmission rates ( P = .29) was shown. Conclusions: This multifaceted intervention improved early discharge and patient experience. Our checklist of key behaviors could be applied throughout other services and hospitals with reproducible success. Level of Evidence: 4 Laryngoscope, 131:E76–E82, 2021